Implementasi Metode Pembelajaran Pecahan Menggunakan Media Visualisasi di Kelas IV Sekolah Dasar Negeri 243 Cicabe - Azalia Zalfa Azura; Edria Al Shahada; Salamah Hujaimah; Silfi Mauludini (Lembaga Pengembangan Kinerja Dosen, 2024)
Fractions have many rules that often cause misunderstanding of the concept. Thus, media is needed to make it easier for students to understand the concept of fractions. The purpose of this study was to analyse the implementation of fraction learning methods using visualisation media in class IV of State Elementary School 243 Cicabe. This research method is quantitative. The sample used in this study was 24 fourth grade students with the object of research, namely the process of learning fractions using visualisation media and students' competence in solving fraction problems that were changed in the form of visualisation. The research method used was field research with data analysed using descriptive analysis. The results showed that the fraction material explained using visualisation media could be understood by the students although when the material level was raised, some students experienced slight difficulties.